Denitrification, Nitrogen Uptake, and Organic Matter Quality Undergo Different Seasonality in Sandy and Muddy Sediments of a Turbid Estuary - Bartoli, Marco; Nizzoli, Daniele; Zilius, Mindaugas; Bresciani, Mariano; Pusceddu, Antonio; Bianchelli, Silvia; Sundbäck, Kristina; Razinkovas-Baziukas, Arturas; Viaroli, Pierluigi (Frontiers in Microbiology, 2021)
The interaction between microbial communities and benthic algae as nitrogen (N) regulators in poorly illuminated sediments is scarcely investigated in the literature. The role of sediments as sources or sinks of N was analysed in spring and summer in sandy and muddy sediments in a turbid freshwater estuary, the Curonian Lagoon, Lithuania. Seasonality in this ecosystem is strongly marked by phytoplankton community succession with diatoms dominating in spring and cyanobacteria dominating in summer. Fluxes of dissolved gas and inorganic N, rates of denitrification of water column nitrate (Dw) and of nitrate produced by nitrification (Dn) and sedimentary features, including the macromolecular quality of organic matter, were measured. Shallow/sandy sites had benthic diatoms, while at deep/muddy sites settled pelagic microalgae were found. The organic matter (OM) in surface sediments was always higher at muddy than at sandy sites, and biochemical analyses revealed that at muddy sites the OM nutritional value changed seasonally. In spring, sandy sediments were net autotrophic and retained N, while muddy sediments were net heterotrophic and displayed higher rates of denitrification, mostly sustained by Dw. In summer, benthic oxygen demand increased dramatically whereas denitrifications, mostly sustained by Dn, decreased in muddy and remained unchanged in sandy sediments. The ratio between denitrification and oxygen demand was significantly lower in sandy compared to muddy sediments and in summer compared to spring. Muddy sediments displayed seasonally distinct biochemical composition with a larger fraction of lipids coinciding with cyanobacteria blooms and a seasonal switch from inorganic N sink to source. Sandy sediments had similar composition in both seasons and retained inorganic N also in summer. Nitrogen uptake by microphytobenthos at sandy sites always exceeded the amount loss via denitrification and benthic diatoms appeared to inhibit denitrification, even in the dark and under conditions of elevated N availability. In spring denitrification attenuated N delivery from the estuary to the coastal area by nearly 35%. In summer denitrification was comparable (~100%) to the much lower N export from the watershed, but N loss was probably offset by large rates of N-fixation.